Entreprenurship For Kids Melalui Pendampingan Kewirausahaan Berbasis Lingkungan Sebagai Sarana Penunjang Experiental Learning Pendidikan Dasar Anak Sejak Dini - Sheellyana Junaedi; Theresia Diah Widiastuti (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Learning entrepreneurship in early childhood can be implemented in an integrated manner with activities at school and at home with parents. One of the stages for introducing children to entrepreneurship, it is necessary to hold a Kidspreneur Education Program which is given to children with the aim of increasing their ability to develop their potential to be beneficial for themselves and for others. The Kidspreneur Education Program is run as a community service program at PAUD Tunas Melati, located in Wonocatur Hamlet, Yogyakarta. PAUD Tunas Melati. Learning methods are carried out using the Experiential Learning method which is carried out for 6 months. The results of this assistance will then become the main capital and productivity of children's independence as adults.